2017
DOI: 10.1111/geb.12561
|View full text |Cite
|
Sign up to set email alerts
|

Geographical patterns of phylogenetic beta‐diversity components in terrestrial mammals

Abstract: Aim To inve stigate geographical patterns of phylogenetic beta diversity (PBD) and its turnover and nestedness-resultant components for terrestrial mammals. We expect an increase in the importance of the nestedness-resultant component towards temperate regions given the historical loss of lineages caused by environmental and spatial constraints. Analogously, we expect to find a similar increase in the contribution of the nestedness-resultant component towards higher elevations. We expect these patterns to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(89 citation statements)
references
References 60 publications
(105 reference statements)
3
85
0
Order By: Relevance
“…Patterns of diversity, however, are scale-dependent, and at broad geographical scales community assembly will also be influenced by biogeographical and evolutionary dynamics affecting the rates of speciation, extinction and dispersal, processes that result in high taxonomic and phylogenetic variation in community composition (Barton et al, 2013;McKnight et al, 2007;Peixoto, Villalobos, Melo, et al, 2017). Hence, the continental scale encompassed by our study may be one reason why our results implicate different processes other than niche underlying the variation in community composition among Neotropical bat communities in comparison with studies conducted at small scales in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of diversity, however, are scale-dependent, and at broad geographical scales community assembly will also be influenced by biogeographical and evolutionary dynamics affecting the rates of speciation, extinction and dispersal, processes that result in high taxonomic and phylogenetic variation in community composition (Barton et al, 2013;McKnight et al, 2007;Peixoto, Villalobos, Melo, et al, 2017). Hence, the continental scale encompassed by our study may be one reason why our results implicate different processes other than niche underlying the variation in community composition among Neotropical bat communities in comparison with studies conducted at small scales in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Within such a scenario, mountain ranges throughout this region have prevented species dispersal, promoting faunal isolation and high beta diversity among communities (Castro-Insua et al, 2016;McKnight et al, 2007;Zuloaga & Kerr, 2017). For example, Diniz-Filho (2009) andPeixoto, Villalobos, Melo, et al (2017) showed that high levels of species and lineage turnover in mammals are found in the highlands and topographically complex regions within the Neotropics, probably because of differential allopatric speciation, extinction and adaptation among different clades to such conditions. In a global analysis of PBD for bats, Peixoto, Braga, Cianciaruso, Diniz-Filho, and Brito (2014) found that their phylogenetic dissimilarity among biogeographical realms is linked mainly to the spatial turnover of lineages, a result similar to which we found for phyllostomid bats in Neotropics.…”
Section: Discussionmentioning
confidence: 99%
“…After calculating pairwise beta diversity for the communities in the different realms, we also calculated beta diversity (taxonomic and phylogenetic) for each cell of the Neotropical and Nearctic realms in order to investigate drivers of beta diversity for each cell and properly evaluate the effects of areas more affected by climatic instability in relation to the LGM. Beta diversity was calculated as the mean beta diversity between each cell and its neighbours, an approach commonly used in recent studies (Melo et al, 2009;Dobrovolski et al, 2012;Wen et al, 2016;Peixoto et al, 2017). This other metric of beta diversity was calculated mainly for these two realms because (1) environmental processes were important in shaping beta diversity in these realms (see results); (2) they are large areas, having a large sample size; and (3) they are well-studied realms where beta diversity patterns have already been evaluated for other clades.…”
Section: Beta Diversitymentioning
confidence: 99%
“…Macroecological studies have evaluated potential drivers of beta diversity patterns on large scales in a wide range of vertebrates. However, although these studies covered a few biogeographical realms (Melo et al ., ; Svenning et al ., ; Dobrovolski et al ., ; Siefert et al ., ) or even global patterns (Buckley & Jetz, ; Leprieur et al ., ; Baselga et al ., ; Peixoto et al ., ), they did not consider whether different processes may influence beta diversity in the different realms (but see Qian & Ricklefs, ). Biogeographical realms are commonly geographically isolated in relation to each other and also have unique histories and diversities, highlighting the occurrence of independent evolution and different processes shaping their diversity (Hawkins et al ., ; Holt et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation